2005
DOI: 10.1099/jmm.0.46095-0
|View full text |Cite
|
Sign up to set email alerts
|

Identification and characterization of Shigella boydii 20 serovar nov., a new and emerging Shigella serotype

Abstract: Analysis of 163 putative Shigella isolates from Canada and the USA showed biochemical reactions consistent with Shigella species, although none of the isolates reacted with antiserum raised against any of the well-established or provisional Shigella serotypes. All these isolates, provisionally designated serotype SH108, were positive for the ipaH gene and the invasion-associated locus. All fermented mannitol, were serologically indistinguishable from each other and showed no reaction in antisera prepared again… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
26
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(29 citation statements)
references
References 22 publications
2
26
0
Order By: Relevance
“…Other studies have shown that class 2 integrons are more prevalent in industrialized and/or emerging countries [23,24,25]. Among shigellae, class 2 integrons tend to be associated with Shigella sonnei [26,20,27,28]. We detected class 1 and 2 integrons in S. dysenteriae, S. flexneri and in the new serovar of S. boydii 20.…”
Section: Discussionmentioning
confidence: 55%
See 2 more Smart Citations
“…Other studies have shown that class 2 integrons are more prevalent in industrialized and/or emerging countries [23,24,25]. Among shigellae, class 2 integrons tend to be associated with Shigella sonnei [26,20,27,28]. We detected class 1 and 2 integrons in S. dysenteriae, S. flexneri and in the new serovar of S. boydii 20.…”
Section: Discussionmentioning
confidence: 55%
“…Previous studies also found similar patterns for S. boydii serotype 20 by using pulsedfield gel electrophoresis and ribotyping, and inferred that this serotype could be homogeneous [28,33].…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…It is common in developing countries where affected populations are immunologically compromised due to poor nutrition and background infections leading to high morbidity attributed to shigellosis [8][9][10]. Salmonellosis, a major cause of bacteria enteric illness in both humans and animals cause diseases in humans and is referred to as a zoonotic infection/disease.…”
Section: Introductionmentioning
confidence: 99%
“…Serotyping is not always able to provide a correct species identification, due to cross-reactions or the absence of agglutination. New serotypes are regularly discovered (28,49) and are sometimes found to cross-react with Escherichia coli strains.…”
mentioning
confidence: 99%